Resin Metal Composite

The resin-metal composite with PBT resin and surface-irregular metal members, enhanced by a polyester resin composition and oxidized polyethylene wax, addresses bonding stability and gas generation issues, enabling broad application suitability.

JP7604851B2Active Publication Date: 2024-12-24MITSUBISHI CHEM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020193562
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-20
Publication Date
2024-12-24
Estimated Expiration
2040-11-20

AI Technical Summary

Technical Problem

Conventional resin-metal composites face challenges in achieving stable bonding states, particularly for automotive applications, and generate unknown gases during industrial production.

Method used

A resin-metal composite structure is developed using a PBT resin member and a metal member with surface irregularities, incorporating a polyester resin composition containing PBT, an epoxy group-containing compound, and oxidized polyethylene wax to enhance bonding stability and reduce gas generation.

Benefits of technology

The composite achieves stable bonding, suitable for a wide range of applications from consumer products to automobiles, with improved industrial production stability and reduced gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604851000012
    Figure 0007604851000012
  • Figure 0007604851000013
    Figure 0007604851000013
  • Figure 0007604851000014
    Figure 0007604851000014
Patent Text Reader

Abstract

To provide a resin-metal composite body having a configuration such that a PBT resin member and a metal member are coupled with each other, in which the bonded state can be made sufficiently stable and further generation of gas during production can be suppressed.SOLUTION: There is provided a resin-metal composite body that comprises: a metal member (X) having surface irregularities; and a resin member (Y) made of a polyester resin composition (A), and that has a structure obtained by coupling a surface side having surface irregularities of the metal member (X) with the resin member (Y), in which the polyester resin composition (A) contains polybutylene terephthalate (also referred to as a homo PBT), a copolymer of polybutylene terephthalate (also referred to as a copolymerized PBT) or a mixed resin thereof as a polyester (a), and further contains an epoxy group-containing compound (b) and a low molecular weight compound (c), and the low molecular weight compound contains polyethylene oxide wax.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin-metal composite body having a configuration in which a PBT resin member, the main component of which is polybutylene terephthalate (also referred to as "PBT"), is bonded to a metal member. [Background technology]

[0002] In recent years, in the fields of automobile parts and consumer parts, development is proceeding in the direction of replacing metal products with resin products, taking into consideration environmental aspects such as weight reduction and recycling. Among resin products, polyester products are widely used in various equipment parts because they have excellent mechanical strength, chemical resistance, and electrical insulation properties, as well as excellent heat resistance, moldability, and recyclability. In particular, thermoplastic polyester resins, such as polybutylene terephthalate, are widely used in electrical and electronic equipment parts that require fire safety, because they have excellent mechanical strength and moldability, and can be made flame retardant.

[0003] However, since resin products have poor heat dissipation properties, development of resin-metal composites in which metal members such as aluminum and iron are bonded to resin members is underway in the fields of electrical and electronic equipment parts, automobile parts, etc. This type of resin-metal composite can generally be made superior to resin products in terms of strength, antistatic properties, thermal conductivity, heat dissipation properties, and electromagnetic wave shielding properties.

[0004] Regarding such a resin-metal composite, for example, Patent Document 1 discloses a method of integrally molding a metal and a thermoplastic resin by in-mold molding a thermoplastic resin onto a metal substrate. Furthermore, Patent Document 2 discloses another method for producing a composite body of a resin member and a metal member, in which a metal part is subjected to a surface treatment by chemical etching, and then a resin is joined to the metal part by injection molding. Patent Document 3 discloses a method for treating metal surfaces that exhibits excellent adhesion when bonding metals to organic polymeric substances, etc., in which a chemical etching treatment is performed on the metal surface, which is accompanied by the formation of a film, and then the film is chemically removed. Furthermore, Patent Document 4 discloses a method for producing a bonded body of a metal substrate and a cured resin, in which a zincate coating is formed on the surface of an aluminum substrate, the surface is roughened using an etching agent, and a resin composition is placed in a recess formed by the roughening. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 6-29669 [Patent Document 2] JP 2008-173967 A [Patent Document 3] Japanese Patent Application Publication No. 11-293476 [Patent Document 4] JP 2019-99864 A Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally known resin-metal composites have had difficulty in expanding their applications because the bond between the metal member and the resin member was not sufficiently stable, and there were problems with their use in automobiles in particular. Incidentally, as disclosed in the above-mentioned Patent Documents 2 to 4, if a metal component is immersed in a chemical solution to roughen the surface of the metal component and provide irregularities, and then resin is filled into the roughened surface by injection molding or the like, not only can the anchor effect of the irregularities be utilized to join the metal component and the resin component, but the process can be carried out regardless of the size or shape of the metal component, thereby expanding the range of applications and allowing the process to be used in, for example, automobiles. However, it has become clear that when the above-mentioned injection molding is carried out continuously for industrial production, gases of unknown origin are generated.

[0007] Therefore, the present invention relates to a resin-metal composite having a configuration in which a PBT resin component made of a resin composition having PBT or a copolymer thereof as the main resin component is joined to a metal component, and aims to provide a new resin-metal composite in which the joined state can be made sufficiently stable and further gas generation during production can be suppressed. [Means for solving the problem]

[0008] The present invention relates to a resin-metal composite comprising a metal member (X) having a surface with surface irregularities, and a resin member (Y) made of a polyester resin composition (A) containing a polyester (a) as a main component resin, the resin member (Y) being bonded to the surface side of the metal member (X) having surface irregularities, The polyester resin composition (A) contains, as a polyester (a), polybutylene terephthalate (also referred to as "homo-PBT"), a copolymer of polybutylene terephthalate (also referred to as "copolymerized PBT"), or a mixed resin thereof, and further contains an epoxy group-containing compound (b) and a low molecular weight compound (c); The present invention proposes a resin-metal composite, characterized in that the low molecular weight compound contains oxidized polyethylene wax. Effect of the Invention

[0009] The resin-metal composite proposed by the present invention is capable of achieving a sufficiently stable bond by selecting a resin member (Y) made of a polyester resin composition (A) containing PBT, a PBT copolymer, or a mixed resin thereof as a main component resin and further containing a bisphenol A type epoxy compound (b) as a resin member (Y) suitable for the surface condition of the metal member (X), i.e., a surface condition having surface irregularities, and bonding the resin member (Y) to the metal member (X). Furthermore, by including oxidized polyethylene wax as the low molecular weight compound (c), gas generation during production, particularly gas generation when the polyester resin composition (A) is heated, can be suppressed. Therefore, the resin-metal composite proposed by the present invention can be used in a wide range of applications, from consumer products to automotive applications, and can be produced industrially. [Brief description of the drawings]

[0010] [Figure 1] 1 is a partial cross-sectional perspective view of a resin-metal composite according to an example of the present invention. FIG. [Diagram 2] FIG. 2 is a partially enlarged cross-sectional view of FIG. [Diagram 3] 1(a) to 1(e) are cross-sectional views illustrating examples of joining methods between a metal member (X) and a resin member (Y). [Figure 4] FIG. 1 is a cross-sectional view showing an example in which the resin-metal composite is applied as a part of a housing for an electrical component for a vehicle. [Diagram 5] FIG. 13 is a top perspective view of a metal member produced in a reference example. [Figure 6] This is a diagram of a resin-metal composite prepared in a reference example, i.e., a resin-metal composite used as a test specimen for airtightness evaluation. The upper figure shows the metal member before the composite was created, the lower left figure is a top oblique view of the same, and the lower right figure is a cross-sectional view. [Figure 7] FIG. 2 is an exploded perspective view of the pressure vessel used in the airtightness evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.

[0012] <<<This resin-metal composite>>> A resin-metal composite according to one embodiment of the present invention (referred to as "the resin-metal composite") is a resin-metal composite comprising a metal member (X) having a surface with surface irregularities on at least one side, and a resin member (Y) made of a polyester resin composition (A) containing polyester (a) as the main resin component, and having a configuration in which the surface side having surface irregularities of the metal member (X) is bonded to the resin member (Y).

[0013] <<Metal parts (X)>> The metal member (X) is a metal member (X) having a surface with projections and recesses (also referred to as an "irregular surface") over the entire surface or a part thereof.

[0014] Examples of metals constituting the metal member (X) include various metals such as aluminum, iron, copper, magnesium, tin, nickel, and zinc, and alloys containing these metals. Among these, it is preferable to include at least one of aluminum, iron, copper, and magnesium, and alloys containing these metals, and it is more preferable to include aluminum and an alloy containing aluminum.

[0015] The shape of the metal member (X) is not particularly limited. For example, it may be flat, curved, plate, rod, tube, block, sheet, film, or any other desired shape. It is not limited to a single flat or curved surface, and may have various shapes such as a stepped portion, a concave portion, or a convex portion.

[0016] The thickness of the metal member (X) is not particularly limited. However, from the viewpoint of product design, it is preferably in the range of 0.05 mm to 50 mm, more preferably 0.10 mm or more or 10 mm or less, and even more preferably 0.12 mm or more or 5 mm or less. In particular, in the case of an aluminum plate or an iron plate, the thickness is preferably 0.10 mm to 10 mm, and even more preferably 0.2 mm or more or 5 mm or less. In this case, the "thickness" refers to the thickness of the metal member (X) which is the thinnest part among the parts to be joined to the resin member (Y) when the metal member is flat and has a uniform thickness. On the other hand, when the metal member is other than flat, i.e., when the thickness is not uniform, the "thickness" refers to the thickness of the thinnest part of the metal member (X) which is to be joined to the resin member (Y).

[0017] <Uneven surface> When the surface of a metal component is roughened with a chemical solution and then bonded to a resin component, it has gradually become clear that there is a compatibility between the surface condition and the type of resin component. In particular, it has become clear that for PBT resin components made of a resin composition whose main resin component is PBT or its copolymer, there is a special compatibility between the composition of the resin composition and the surface condition of the metal component.

[0018] From this viewpoint, the surface of the metal member (X), i.e., the surface to be bonded to the resin member (Y), preferably has an arithmetic mean roughness (Ra) measured in accordance with JIS B 0601:2001 of 0.05 μm or more, more preferably 0.1 μm or more, particularly 0.2 μm or more, also 0.3 μm or more, further 0.4 μm or more, of which 0.5 μm or more, and most preferably 1 μm or more. The upper limit of the arithmetic mean roughness (Ra) is preferably 200 μm or less, more preferably 180 μm or less, further preferably 150 μm or less, particularly 120 μm or less, also 100 μm or less, of which 80 μm or less, and 50 μm or less, of which 30 μm or less, and most preferably 10 μm or less. Furthermore, the maximum height (Rz) is preferably 0.01 μm or more, more preferably 0.05 μm or more, and thereafter, successively, 0.1 μm or more, 0.3 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, and most preferably 10 μm or more. The upper limit of the maximum height (Rz) is preferably 200 μm or less, more preferably 180 μm or less, particularly 150 μm or less, and also 120 μm or less, among which 100 μm or less, and 80 μm or less, and most preferably 50 μm or less.

[0019] It has been found that when the surface of the metal member (X) is in such a rough surface state and has irregularities, a strong bonding strength can be achieved by selecting a resin composition of a specific composition. On the other hand, when the surface roughness is out of the above range, the composition of the resin composition that is compatible with the surface roughness is different. For example, when the surface roughness is out of the above range, even if a specific polyester (a) is combined with a specific epoxy group-containing compound (b), the effect of the epoxy group-containing compound (b) may not be confirmed.

[0020] The arithmetic mean roughness (Ra) and maximum height (Rz) of the metal member (X) can be calculated by observing the uneven surface of the surface-treated metal member (X) with a 20x objective lens of a hybrid laser microscope (LASERTEC OPTELICS HYBRID) and measuring the surface roughness in accordance with JIS B 0601:2001 using the attached analysis software (Lasertec Microscope Solution Software LMeye7) at a 20x objective lens. In the specific measurement in the examples, the average uneven surface at the center of a rectangular metal plate material with a length of 45 mm, width of 12 mm, and thickness of 1.5 mm was measured using the measurement algorithm Fine Peak to obtain an FZ image. The measurement range was 4.2 mm long in the direction of the length of 45 mm. The cutoff value λc was 0.8000 mm. The same operation was repeated 30 times at different arbitrary locations, and the average value was calculated. In addition, when measuring the uneven surface of the metal member (X) in this resin-metal composite, the unevenness of the surface of the metal member (X) that is not affected by the joining is measured in the same manner. If there are no unjoined areas, the cross section of this resin-metal composite joined to the resin member (Y) can be observed and measured with an optical microscope or a scanning electron microscope to obtain values ​​corresponding to the arithmetic mean roughness (Ra) and maximum height (Rz).

[0021] The recesses present on the surface of the metal member (X) do not need to have a uniform opening diameter and depth. Recesses of several different sizes (roughness, height, etc.) may be distributed in combination. Specifically, for example, in the case of unevenness with an arithmetic mean roughness Ra of 1 μm to 10 μm and a maximum height Rz of 10 μm to 50 μm, a surface having both recesses with an opening diameter and / or depth of 50 μm to 200 μm and recesses with an opening diameter and / or depth of 0.5 μm to 10 μm is preferable from the viewpoint of obtaining a high bonding strength, rather than having only recesses with a uniform opening diameter and / or depth.

[0022] The metal member (X) and the resin member (Y) may be bonded to the metal member (X) over the entire uneven surface of the metal member (X), or may be bonded to the resin member (Y) over only a portion of the uneven surface. Furthermore, the surface of the metal member (X) does not need to have irregularities at all points where the resin member (Y) and the metal member (X) are in contact with each other. In other words, it is sufficient that the surface of the metal member (X) has irregularities at some of the points where the metal member (X) and the resin member (Y) are joined.

[0023] (Surface roughening method) The method for roughening the entire or part of the surface of the metal member (X) to provide irregularities is not particularly limited, and any known method can be used. Among them, it is preferable to use a chemical solution treatment method in which the metal member (X) is immersed in a chemical solution or coated with a chemical solution, from the viewpoint of being able to treat the metal member (X) regardless of its size or shape. The surface roughening method may be a single method or a combination of multiple methods. By combining multiple methods, it may be possible to achieve effects such as optimization of the uneven structure and cost reduction.

[0024] Various chemical treatment methods are known depending on the type of metal, and known methods can be used. When the metal member (X) is aluminum, an aluminum alloy, or cast aluminum, it is preferable to form a film on the metal surface before forming the unevenness, and then remove the film to form the unevenness. Furthermore, it is preferable to apply a chemical conversion film after forming the unevenness in order to increase the bonding strength.

[0025] Among them, the chemical solution treatment method for forming the uneven surface may include a method in which a zincate film is formed on the surface of the metal member (X) as necessary, and then an etching agent containing peroxodisulfate ions and chloride ions is brought into contact with the surface of the metal member (X).

[0026] The etching agent may be an aqueous solution containing at least peroxodisulfate ions and chloride ions. The etching agent may contain elements such as aluminum, magnesium, silicon, titanium, chromium, manganese, iron, nickel, copper, and zinc derived from the substrate. In addition, elements such as zinc may be mixed in the etching agent by dissolving the coating formed in the zincate process described below.

[0027] The etching agent preferably contains peroxodisulfate ions at a ratio of 0.02 mol / L or more and 0.90 mol / L or less, more preferably 0.10 mol / L or more or 0.50 mol / L or less, and even more preferably 0.15 mol / L or more or 0.40 mol / L or less. The etching agent is chloride ions (Cl -) in a ratio of 0.40 mol / L or more and 2.50 mol / L or less, more preferably 0.80 mol / L or more or 2.00 mol / L or less, and even more preferably 1.20 mol / L or more or 1.70 mol / L or less. As the chloride ion source, one or more suitable compounds may be selected from, for example, lithium chloride, sodium chloride, potassium chloride, calcium chloride, ammonium chloride, and the like.

[0028] The etching agent may be substantially free of phosphoric acid, where substantially free means that the amount of phosphoric acid is below the detection limit.

[0029] The pH of the etching agent is preferably in the range of 6.0 or less, more preferably in the range of 2.0 to 4.0. The pH of the etching agent can be measured using any commercially available pH measuring device and electrode without any limitation. In addition, if a pH measuring device and an electrode having a temperature compensation function are used, and the internal solution of the pH electrode and a commercially available pH standard solution are adjusted to the same temperature as the etching agent, etc., and the pH measuring device is calibrated, the pH at the temperature at which the etching agent, etc. is used can also be measured.

[0030] During etching, the etching agent is adjusted to a liquid temperature of 10 to 70° C., and the metal member (X) is immersed therein.

[0031] When forming a zincate coating on the surface of the metal member (X), for example, a sodium hydroxide solution in which zinc oxide is dissolved is used, the bath temperature is kept at 40.0°C or less, and the metal member (X) is immersed for about 1.0 seconds to 5.0 minutes to remove the natural oxide film and form the zincate coating at the same time. In addition, the formed coating may be dissolved with the etching agent or nitric acid, and the coating may be formed again one or more times. In addition to the essential components, the treatment solution used in these zincate processes may contain metals such as aluminum, magnesium, silicon, titanium, chromium, manganese, iron, nickel, copper, and zinc derived from the substrate. The pH of the treatment solution used for forming the zincate coating is not limited as long as it is within a known range, and for example, in the case of a treatment solution showing an alkaline pH, it may be 10.0 or more, or 13.0 or more. It is preferably within the range of 11.0 to 13.0. In order to adjust the pH of the zincate solution, the pH can be increased using sodium hydroxide or potassium hydroxide.

[0032] Before the treatment with the etching agent or the formation of the zincate film, the surface of the metal member (X) may be cleaned. For example, the surface may be degreased using a solvent-based, water-based, or emulsion-based degreaser. Alternatively, the surface may be washed with an alkali.

[0033] <Top surface layer> The uneven surface of the metal member (X) may be coated with an oxide film, a chemical conversion film (phosphate film, chromate film, silicate film, lithium chemical conversion film, calcium chemical conversion film, zirconium oxide film, etc.), anodized film, or other film, or may have a plating layer, a silane coupling agent treatment layer, a primer layer, a resin layer, or other layer formed thereon, or may have fine particles or the like fixed thereto. Next, the outermost surface layer of the uneven surface of the metal member (X) will be described in detail.

[0034] (Oxide film) The uneven surface of the metal member (X) may be either non-oxidized or oxidized.

[0035] (chemical conversion coating) The uneven surface of the metal member (X) may be subjected to chemical conversion treatment and provided with a chemical conversion coating. By carrying out such a treatment, the adhesion (adhesiveness or adhesive strength) between the metal member (X) and the resin member (Y) can be further improved. Examples of the chemical conversion treatment method include chemical conversion treatment using chromate phosphate or the like, zirconium phosphate treatment, boehmite treatment, zincate treatment, and anodizing treatment. Examples of the anodizing treatment include a treatment thin film using phosphoric acid, phosphoric acid-sulfuric acid, phosphoric acid-oxalic acid, phosphoric acid-chromic acid, etc. Among these, phosphoric acid anodizing treatment is preferred.

[0036] The thickness of the chemical conversion coating is not particularly limited, but is preferably, for example, 1 nm to 300 nm, and more preferably 5 nm or more from the viewpoint of maintaining good processability. When the chemical conversion coating is formed by anodizing, the thickness is preferably in the range of 0.05 μm to 2 μm, more preferably 0.1 μm or more or 2 μm or less, from the viewpoint of more effectively improving adhesion. The thickness of the chemical conversion coating layer formed by anodizing can be adjusted to fall within the above range by adjusting the treatment conditions, particularly the current application conditions and current application time.

[0037] (plating layer) The uneven surface of the metal member (X) may be subjected to a plating treatment such as single-layer plating, multi-layer plating, alloy plating, etc. Prior to these plating treatments, immersion chromate treatment or phosphate chromate treatment may be performed. The plating method may be either electroplating or electroless plating. For example, when the metal substrate is iron, zinc, tin, nickel or copper plating is preferred, and zinc plating is more preferred.

[0038] (Silane coupling agent treated layer) The uneven surface of the metal member (X), particularly when the metal member (X) is made of aluminum, iron or the like, is preferably treated with a silane coupling agent to form a silane coupling agent treatment layer. The silane coupling agent is not particularly limited. For example, compounds having a methoxy group, an ethoxy group, a silanol group, etc. can be mentioned. As the silane coupling agent, vinyltrimethoxysilane, chloropropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(N-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, ureidoaminopropylethoxysilane, etc. can be preferably mentioned. In particular, the aluminum substrate or iron substrate and the silane coupling agent form Al-O-Si or Fe-O-Si bonds to bond strongly, and the polyester (a) of the polyester resin composition (A) and the organic functional group of the silane coupling agent react to bond strongly, so that a stronger bond can be achieved.

[0039] (Primer layer) A primer layer may be provided on the uneven surface of the metal member (X). Examples of materials used for the primer layer include acrylic materials, epoxy materials, urethane materials, and polyamide materials. An example of a commercially available material for the primer layer is Aronmelt PPET manufactured by Toagosei Co., Ltd.

[0040] <<Resin parts (Y)>> The resin member (Y) is a member made of a polyester resin composition (A) containing a polyester (a) as a main component resin. The "main component resin" means a resin or resin group that has the largest content by mass among the resins constituting the polyester resin composition (A), and includes the case where the polyester (a) accounts for 50 mass% or more, particularly 75 mass% or more, and particularly 90 mass% or more (including 100 mass%) of the resins constituting the polyester resin composition (A). However, the polyester (a) may be two or more kinds of polyesters (resin groups).

[0041] The resin member (Y) is made of the polyester resin composition (A) and may have a structure consisting of only the polyester resin composition (A), or may have a structure consisting of multiple materials in which another resin layer, etc. is bonded to the back side of a member or layer consisting of the polyester resin composition (A).

[0042] The size, shape, thickness, etc. of the resin member (Y) are not particularly limited, and may be, for example, a plate shape (disk, polygon, etc.), a column shape, a box shape, a bowl shape, a tray shape, etc. One of the features of this resin-metal composite is that the resin member (Y) can be molded into any shape. The resin member (Y) does not need to have a uniform thickness throughout its entirety, and may be provided with any shaped portion such as a reinforcing rib, if necessary.

[0043] <Polyester resin composition (A)> The polyester resin composition (A) is preferably a resin composition containing, as the polyester (a), polybutylene terephthalate (also called "homo PBT"), a copolymer of polybutylene terephthalate (also called "copolymer PBT"), or a mixed resin thereof, further containing an epoxy group-containing compound (b) and a low molecular weight compound (c), and further containing a reinforcing filler (d) as necessary. An impact modifier may also be included. It can be assumed that the reaction between the terminal functional groups (carboxyl groups) of the homo-PBT and / or copolymer PBT and the epoxy groups of the epoxy group-containing compound (b) increases the airtightness of the resin-metal composite of the resin member (Y) and the metal member (X) after a thermal shock test.

[0044] The polyester resin composition (A) preferably contains the homo-PBT and copolymer-PBT in a proportion of 80 to 100% by mass of the polymer components (excluding the elastomer and the flame retardant) that constitute the composition. It is preferable that the homo-PBT and copolymer-PBT account for most of the composition, that is, that the content ratio of these is 80% by mass or more, because the basic physical properties are improved. From this viewpoint, the proportion of the homo-PBT and copolymer PBT is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more.

[0045] From the viewpoint of moldability, the intrinsic viscosity of the polyester resin composition (A) is preferably 0.30 to 2.00 dl / g, more preferably 0.40 dl / g or more, and even more preferably 0.60 dl / g or more, while it is preferably 1.80 dl / g or less, and even more preferably 1.50 dl / g or less. In the present invention, the intrinsic viscosity is a value measured at 30° C. in a mixed solvent of tetrachloroethane and phenol in a 1:1 (mass ratio). The intrinsic viscosity of the polyester resin composition (A) can be adjusted by changing the molecular weight of the polyester (a), although this is not limitative.

[0046] <Polyester (a)> The polyester (a) as the main component resin is preferably polybutylene terephthalate (also referred to as "homo PBT"), a copolymer of polybutylene terephthalate (also referred to as "copolymer PBT"), or a mixed resin thereof.

[0047] From the viewpoint of moldability, the intrinsic viscosity of the polyester (a) is preferably 0.30 to 2.00 dl / g, more preferably 0.40 dl / g or more, and even more preferably 0.60 dl / g or more, while it is preferably 1.80 dl / g or less, and even more preferably 1.50 dl / g or less. The intrinsic viscosity of the polyester (a) can be adjusted by changing the molecular weight of the polyester (a), but is not limited thereto.

[0048] (Homo PBT) Homo PBT is a polymer having a structure in which terephthalic acid units and 1,4-butanediol units are ester-bonded, and is a polymer composed of terephthalic acid units and 1,4-butanediol units.

[0049] The amount of terminal carboxyl groups in the homo-PBT is preferably 60 eq / ton or less, more preferably 50 eq / ton or less, and even more preferably 30 eq / ton or less. The amount of terminal carboxyl groups in a polybutylene terephthalate homopolymer can be determined by dissolving 0.5 g of the resin in 25 mL of benzyl alcohol and titrating the resultant solution with a 0.01 mol / l solution of sodium hydroxide in benzyl alcohol. The amount of terminal carboxyl groups may be adjusted by any conventional method, such as adjusting polymerization conditions such as the raw material charging ratio during polymerization, polymerization temperature, and pressure reduction method, or by reacting a terminal blocking agent.

[0050] The number average molecular weight of the homo-PBT is preferably 7000 or more, more preferably 8000 or more, and even more preferably 9000 or more, while it is preferably 20000 or less, more preferably 19000 or less, and even more preferably 17000 or less.

[0051] The intrinsic viscosity of the homo-PBT is preferably 0.30 to 2.00 dl / g. If the intrinsic viscosity is 0.30 dl / g or more, the mechanical strength of the welded body will not become too low, and if it is 2.00 dl / g or less, it is possible to prevent a decrease in fluidity, which would result in a deterioration in moldability or a decrease in bonding strength. From this viewpoint, the intrinsic viscosity of the homo-PBT is preferably 0.30 to 2.00 dl / g, more preferably 0.40 dl / g or more, and even more preferably 0.60 dl / g or more, while it is preferably 1.80 dl / g or less, and even more preferably 1.50 dl / g or less.

[0052] (Copolymerized PBT) Copolymer PBT is a polybutylene terephthalate copolymer that contains other copolymer components other than terephthalic acid units and 1,4-butanediol units.

[0053] Specific examples of dicarboxylic acid units other than terephthalic acid include aromatic dicarboxylic acids such as isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-3,3'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, bis(4,4'-carboxyphenyl)methane, anthracenedicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid and 4,4'-dicyclohexyldicarboxylic acid; and aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, and dimer acid.

[0054] Examples of diol units other than 1,4-butanediol include aliphatic or alicyclic diols having 2 to 20 carbon atoms, bisphenol derivatives, etc. Specific examples include ethylene glycol, propylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, decamethylene glycol, cyclohexanedimethanol, 4,4'-dicyclohexylhydroxymethane, 4,4'-dicyclohexylhydroxypropane, and ethylene oxide adduct diol of bisphenol A.

[0055] From the viewpoint of mechanical properties and heat resistance, the copolymer PBT preferably contains terephthalic acid in the dicarboxylic acid units at a ratio of 70 mol % or more, and more preferably 90 mol % or more. The proportion of 1,4-butanediol in the diol units is preferably 70 mol % or more, and more preferably 90 mol % or more.

[0056] In addition to the bifunctional monomers described above, the copolymerized PBT may contain a small amount of polyfunctional monomers, such as tricarballylic acid, trimellitic acid, trimellitic acid, etc., trifunctional acids capable of forming esters, such as pyromellitic acid, etc., in order to introduce a branched structure, or trifunctional or tetrafunctional alcohols capable of forming esters, such as glycerin, trimethylolpropane, pentaerythritol, etc., or monofunctional compounds, such as fatty acids, in order to adjust the molecular weight.

[0057] The copolymerized PBT can be modified by a copolymerization component. For example, examples of the copolymerization component include polybutylene terephthalate resin copolymerized with polyalkylene glycols (particularly polytetramethylene glycol (PTMG)), and dimer acid copolymerized polybutylene terephthalate resin, particularly isophthalic acid copolymerized polybutylene terephthalate resin.

[0058] In the copolymerized PBT copolymerized with polytetramethylene glycol (PTMG), the ratio of the tetramethylene glycol component in the copolymer is preferably 3 to 40 mass%, more preferably 5 mass% or more or 30 mass% or less, and even more preferably 10 mass% or more or 25 mass% or less. By setting the copolymerization ratio in this manner, it is preferable because it tends to have an excellent balance between bonding strength and heat resistance. On the other hand, in the case of copolymerized PBT in which dimer acid is copolymerized, the ratio of dimer acid components to all carboxylic acid components is preferably 0.5 to 30 mol % as carboxylic acid groups, more preferably 1 mol % or more or 20 mol % or less, and even more preferably 3 mol % or more or 15 mol % or less. By setting the copolymerization ratio in this way, the balance of bonding strength, long-term heat resistance, and toughness tends to be excellent, which is preferable. In the case of copolymerized PBT in which isophthalic acid is copolymerized, the ratio of isophthalic acid components to all carboxylic acid components is preferably 1 to 30 mol % as carboxylic acid groups, more preferably 2 mol % or more or 20 mol % or less, and even more preferably 3 mol % or more or 15 mol % or less. By setting the copolymerization ratio in this way, the balance of bonding strength, heat resistance, injection moldability, and toughness tends to be excellent, which is preferable. As the copolymer PBT, from the viewpoint of moldability, a copolymer PBT copolymerized with polytetramethylene glycol or a copolymer PBT copolymerized with isophthalic acid is particularly preferable.

[0059] The number average molecular weight of the copolymerized PBT is preferably 5000 or more, more preferably 6000 or more, and even more preferably 8000 or more. On the other hand, it is preferably 20000 or less, more preferably 19000 or less, and even more preferably 17000 or less.

[0060] The intrinsic viscosity of the copolymer PBT is preferably 0.30 to 2.00 dl / g. If the intrinsic viscosity is 0.30 dl / g or more, the mechanical strength of the welded body will not become too low, and if it is 2.00 dl / g or less, it is possible to prevent a decrease in fluidity, which would result in a deterioration in moldability or a decrease in bonding strength. From this viewpoint, the intrinsic viscosity of the copolymer PBT is preferably 0.30 to 2.00 dl / g, more preferably 0.40 dl / g or more, and even more preferably 0.60 dl / g or more, while it is preferably 1.80 dl / g or less, and even more preferably 1.50 dl / g or less.

[0061] The amount of terminal carboxyl groups in the copolymerized PBT is preferably 60 eq / ton or less. If the amount of terminal carboxyl groups is 60 eq / ton or less, gas generation during melt molding of the resin composition can be suppressed. From this viewpoint, the amount of terminal carboxyl groups in the copolymer PBT is preferably 60 eq / ton or less, more preferably 50 eq / ton or less, and even more preferably 30 eq / ton or less. On the other hand, there is no particular lower limit for the amount of terminal carboxyl groups, and it is usually 5 eq / ton or more. The amount of terminal carboxyl groups in the copolymer PBT can be determined by dissolving 0.5 g of the resin in 25 mL of benzyl alcohol and titrating the solution with a 0.01 mol / l solution of sodium hydroxide in benzyl alcohol. The amount of terminal carboxyl groups may be adjusted by any conventional method, such as adjusting polymerization conditions such as the raw material charging ratio during polymerization, polymerization temperature, and pressure reduction method, or by reacting a terminal blocking agent.

[0062] (Homo PBT + Copolymer PBT) The polyester (a) may be a mixed resin of homo-PBT and copolymer-PBT. In this case, the mixing ratio of the copolymer PBT to the mixed resin is preferably 0.1 mol% or more and 30 mol% or less with respect to the total monomers, more preferably 1 mol% or more or 25 mol% or less, and even more preferably 5 mol% or more or 20 mol% or less. As for the mass ratio, the mixing ratio of homo-PBT / copolymer is preferably 99 / 1 to 1 / 99 (mass ratio), more preferably 95 / 5 to 5 / 95 (mass ratio), and even more preferably 90 / 10 to 10 / 90 (mass ratio).

[0063] <Epoxy group-containing compound (b)> The epoxy group-containing compound (b) does not necessarily contribute to the initial bonding strength, but it improves the required durability based on the bonding strength after the durability test. The durability is greatly improved by including the epoxy group-containing compound (b). This durability is not reduced even by including the low molecular weight compound (c).

[0064] Preferred examples of the epoxy group-containing compound (b) include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, resorcinol type epoxy compounds, novolac type epoxy compounds, alicyclic compound type diepoxy compounds, glycidyl ethers, and epoxidized polybutadienes. More specifically, preferred examples of the epoxy group-containing compound (b) include alicyclic compound type epoxy compounds such as bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, resorcinol type epoxy compounds, novolac type epoxy compounds, vinylcyclohexene dioxide, and dicyclopentadiene oxide.

[0065] Among these, in terms of compatibility with homo-PBT and / or copolymer PBT, 2,2-bis(4-hydroxyphenyl)-propane type epoxy compounds (also referred to as "bisphenol A type epoxy compounds") or novolac type epoxy compounds are preferred, and bisphenol A type epoxy compounds are particularly preferred.

[0066] Among these, the epoxy equivalent (mass (g) per mole of epoxy groups contained in the epoxy compound) of the bisphenol A type epoxy compound and the novolac type epoxy compound is preferably 50 to 1000 g / eq. from the viewpoint of improving bonding strength, and more preferably 70 g / eq. or more, and even more preferably 100 g / eq. or more, while more preferably 900 g / eq. or less, and even more preferably 800 g / eq. or less.

[0067] In addition, the number average molecular weight of the bisphenol A type epoxy compound and the novolac type epoxy compound is preferably 100 to 2000, more preferably 150 or more, and even more preferably 200 or more, from the viewpoint of fluidity, and is preferably 1800 or less, and even more preferably 1600 or less.

[0068] From the viewpoints of improving bonding strength and fluidity, the epoxy group-containing compound (b) is preferably contained in an amount of 0.001 to 35 parts by mass relative to 100 parts by mass of the polyester (a), and more preferably 0.01 part by mass or more, even more preferably 0.1 part by mass or more, and even more preferably 0.3 parts by mass or more, while more preferably 25 parts by mass or less, even more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 6 parts by mass or less.

[0069] From the viewpoint of improving the bonding strength, the epoxy group-containing compound (b) is preferably contained in an amount of 0.1 to 10 equivalents of epoxy groups relative to the amount of terminal carboxyl groups in the homo-PBT and / or copolymer PBT which is the polyester (a), and more preferably contains an epoxy group in an amount of 0.15 equivalents or more, and even more preferably contains an epoxy group in an amount of 0.2 equivalents or more, while more preferably contains an epoxy group in an amount of 8.0 equivalents or less, and even more preferably contains an epoxy group in an amount of 7.0 equivalents or less, and even more preferably contains an epoxy group in an amount of 6.0 equivalents or less.

[0070] <Low molecular compound (c)> If the polyester resin composition (A) further contains a low molecular weight compound (c) having a number average molecular weight of less than 6,000, the bonding strength of the resin-metal composite can be further increased.

[0071] The number average molecular weight of the low molecular weight compound (c) is preferably less than 6000, more preferably at least 50, and even more preferably at least 100. On the other hand, it is preferably not more than 5000, more preferably not more than 4500, and even more preferably not more than 4200.

[0072] Examples of the low molecular weight compound (c) include one or more low molecular weight compounds selected from polyolefin-based compounds, aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds, and silicone-based compounds.

[0073] The polyolefin-based compound may be a compound selected from paraffin wax and polyethylene wax, or may be a modified polyolefin-based compound having a hydroxyl group, a carboxyl group, an anhydride group, an epoxy group, or the like introduced into a side chain.

[0074] The aliphatic carboxylic acid may be, for example, a saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acid. Here, the aliphatic carboxylic acid includes an alicyclic carboxylic acid. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.

[0075] As the aliphatic carboxylic acid in the ester of the aliphatic carboxylic acid and the alcohol, for example, the same aliphatic carboxylic acid as the above can be used. On the other hand, examples of alcohols include saturated or unsaturated monohydric or polyhydric alcohols. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, monohydric or polyhydric saturated alcohols having 30 or less carbon atoms are preferred, and aliphatic saturated monohydric alcohols or aliphatic saturated polyhydric alcohols having 30 or less carbon atoms are more preferred. Here, aliphatic includes alicyclic compounds. Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.

[0076] The ester of the aliphatic carboxylic acid and the alcohol may contain the aliphatic carboxylic acid and / or the alcohol as impurities. The ester may be a pure substance or a mixture of a plurality of compounds. The aliphatic carboxylic acid and the alcohol that are combined to form an ester may each be one type, or two or more types may be used in any combination and ratio.

[0077] Specific examples of esters of aliphatic carboxylic acids and alcohols include montan acid ester wax, beeswax (a mixture containing myricyl palmitate as a main component), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.

[0078] Examples of the aliphatic hydrocarbon compound include liquid paraffin, paraffin wax, microcrystalline wax, polyolefin wax such as polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. Here, the aliphatic hydrocarbons include alicyclic hydrocarbons. These hydrocarbons may be partially oxidized. The aliphatic hydrocarbon compound may be a single substance or a mixture of substances with various constituent components and molecular weights, and any substance may be used as long as the main component is within the above range.

[0079] The silicone-based compound may be, for example, a modified silicone oil, such as a silicone oil having an organic group introduced into the side chain of a polysiloxane, or a silicone oil having an organic group introduced into both ends and / or one end of a polysiloxane, etc. In this case, examples of the organic group introduced include an epoxy group, an amino group, a carboxyl group, a carbinol group, a methacryl group, a mercapto group, a phenol group, etc., and preferably an epoxy group. As the modified silicone oil, a silicone oil in which an epoxy group is introduced into the side chain of polysiloxane is particularly preferable.

[0080] As the low molecular weight compound, polyolefin wax is particularly preferred from the viewpoint of low gas generation and suppression of gas generation. The polyolefin wax may be any conventionally known one, and examples thereof include (co)polymers (meaning polymerization or copolymerization; the same applies below) containing one type of olefin or two or more types in any ratio, preferably having 2 to 30 carbon atoms, more preferably 2 to 12, and even more preferably 2 to 10 carbon atoms.

[0081] Examples of the olefin having 2 to 30 carbon atoms include ethylene, propylene, α-olefins having 4 to 30 carbon atoms (preferably 4 to 12, more preferably 4 to 10), and dienes having 4 to 30 carbon atoms (preferably 4 to 18, more preferably 4 to 8). Examples of the α-olefins include 1-butene, 4-methyl-1-pentene, 1-pentene, 1-octene, 1-decene, and 1-dodecene. Examples of the diene include butadiene, isoprene, cyclopentadiene, and 11-dodecadiene.

[0082] As the polyolefin wax, polyethylene wax is preferred from the viewpoints of low gas generation, suppression of gas generation, improvement of bonding strength, and heat resistance. The polyethylene wax can be produced by any method, for example, by polymerization of ethylene or thermal decomposition of polyethylene.

[0083] As the low molecular weight compound, those having an acid value of 0.01 to 40 mgKOH / g are preferred because they have a significant effect of improving the bonding strength and have a small volatile content. The acid value is more preferably 0.01 to 35 mgKOH / g, and even more preferably 0.5 to 32 mgKOH / g. As long as the acid value is within the range of 0.01 to 40 mgKOH / g, a compound having an acid value of less than 0.01 mgKOH / g and a compound having an acid value of more than 40 mgKOH / g may be used in combination, provided that the acid value of the multiple types of low molecular weight compounds as a whole is 0.01 to 40 mgKOH / g.

[0084] Examples of the low molecular weight compound having an acid value of 0.01 to 40 mgKOH / g include esters of the above-mentioned aliphatic carboxylic acids and alcohols having an acid value of 0.01 to 40 mgKOH / g, and the above-mentioned aliphatic hydrocarbon compounds, preferably modified polyolefin waxes in which functional groups having affinity for polyester resins, such as carboxyl groups (representing carboxylic acid (anhydride) groups, i.e., carboxylic acid groups and / or carboxylic acid anhydride groups; the same applies below), haloformyl groups, ester groups, carboxylate metal bases, hydroxyl groups, alkosyl groups, epoxy groups, amino groups, amide groups, etc., are imparted to the above-mentioned polyolefin waxes.

[0085] The carboxyl group used to modify the polyolefin wax may include low molecular weight compounds containing a carboxylic acid group, such as maleic acid, maleic anhydride, acrylic acid, and methacrylic acid, low molecular weight compounds containing a sulfo group, such as sulfonic acid, and low molecular weight compounds containing a phospho group, such as phosphonic acid. Among these, low molecular weight compounds containing a carboxylic acid group are preferred, and maleic acid, maleic anhydride, acrylic acid, and methacrylic acid are particularly preferred. These carboxylic acids may be used alone or in combination of two or more in any ratio. The amount of acid added to the modified polyolefin wax is usually 0.01 to 10% by mass, and preferably 0.05 to 5% by mass, based on the modified polyolefin wax.

[0086] Specific examples of the haloformyl group include a chloroformyl group, a bromoformyl group, etc. Any conventional method may be used to provide these functional groups to the polyolefin wax, and specific examples of the method include copolymerization with a compound having a functional group, post-processing such as oxidation, and the like. The type of functional group is preferably a carboxyl group, since it has an appropriate affinity with polyester resins.

[0087] The concentration of the carboxyl group in the modified polyolefin wax may be appropriately selected and determined, but if it is too low, the affinity with the polyester resin is low, the effect of suppressing volatile matter is low, and the bonding strength may decrease. Conversely, if the concentration is too high, for example, the polymer main chain constituting the polyolefin wax is excessively cut during modification, and the molecular weight of the modified polyolefin wax is reduced too much, resulting in the generation of a large amount of volatile matter, and the surface of the polyester resin molded body may become cloudy. The modified polyolefin wax is preferably an oxidized polyethylene wax.

[0088] Among the above, the low molecular weight compound (c) preferably has a melting point of 40 to 140°C, more preferably 45°C or higher, and even more preferably 50°C or higher, while it preferably has a melting point of 135°C or lower, and even more preferably 130°C or lower.

[0089] The low molecular weight compound may be contained in one type or in any combination and ratio of two or more types.

[0090] The low molecular weight compound (c) is preferably contained in an amount of 0 to 1.5 parts by mass, more preferably 0.001 to 1.5 parts by mass, relative to 100 parts by mass of the polyester resin composition (A), and of these, 0.01 part by mass or more, particularly 0.1 part by mass or more, even more preferably 0.2 parts by mass or more, while of these, 1.4 parts by mass or less, even more preferably 1.2 parts by mass or less.

[0091] (Oxidized polyethylene wax) Among the above low molecular weight compounds (c), oxidized polyethylene wax is most preferred from the viewpoint of suppressing gas generation when the polyester resin composition (A) is heated.

[0092] Oxidized polyethylene wax is a compound obtained by oxidizing polyethylene and introducing polar groups. Examples of the polar group include a carboxyl group, an amino group, and a hydroxyl group.

[0093] From the viewpoint of suppressing gas generation when the polyester resin composition (A) is heated, the number average molecular weight of the oxidized polyethylene wax is preferably 1500 or more, more preferably 2000 or more, more preferably 2500 or more, more preferably 3000 or more, and even more preferably 3500 or more. On the other hand, from the viewpoint of improving the bonding strength, the number average molecular weight is preferably 5000 or less, more preferably 4500 or less, and even more preferably 4200 or less.

[0094] From the viewpoint of suppressing gas generation when the polyester resin composition (A) is heated, the acid value of the oxidized polyethylene wax is preferably 0.01 to 40 mgKOH / g, more preferably 0.1 mgKOH / g or more or 30 mgKOH / g or less, even more preferably 0.5 mgKOH / g or more or 20 mgKOH / g or less, and even more preferably 0.7 mgKOH / g or more or 10 mgKOH / g or less.

[0095] From the viewpoint of suppressing gas generation when the polyester resin composition (A) is heated, the oxidized polyethylene wax as the low molecular weight compound (c) is preferably contained in an amount of 0.001 to 1.5 parts by mass, particularly preferably 0.01 to 1.5 parts by mass, and even more preferably 0.1 part by mass or more or 1.0 part by mass or less, and even more preferably 0.2 part by mass or more or 0.7 part by mass or less, relative to 100 parts by mass of the polyester resin composition (A).

[0096] <Other resin components> The polyester resin composition (A) may contain other resins in addition to the above, for example, one or a combination of two or more selected from the group consisting of carbodiimide compounds, compounds having an oxazoline group (ring), compounds having an oxazine group (ring), compounds having a carboxylic acid, and compounds having an amide group. In addition, for example, polyamide resin, polyphenylene oxide resin, polyphenylene sulfide resin, polysulfone resin, polyethersulfone resin, polyetherimide resin, polyetherketone resin, fluororesin, etc. may also be included. However, the proportion of other resins in the polyester resin composition (A) is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0097] (Carbodiimide compounds) The carbodiimide compound is a compound containing a carbodiimide group (-N=C=N-) in the molecule. As the carbodiimide compound, any of aliphatic carbodiimide compounds having an aliphatic main chain, alicyclic carbodiimide compounds having an alicyclic main chain, and aromatic carbodiimide compounds having an aromatic main chain can be used. Among them, the use of alicyclic carbodiimide compounds is preferred in that the hydrolysis resistance of the resin-metal composite can be improved. The carbodiimide compound may be of either a monomeric type or a polymeric type, but in the present invention, the polymeric type is preferred. In the case of a polymer type carbodiimide, the number average molecular weight is preferably 10,000 or less, more preferably 4,000 or less, and the lower limit is preferably 100 or more, more preferably 500 or more.

[0098] The content of carbodiimide groups contained in the carbodiimide compound is, in terms of carbodiimide equivalent (weight [g] of the carbodiimide compound required to provide 1 mol of carbodiimide groups), preferably 100 to 1000 (g / 1 mol), more preferably 200 (g / 1 mol) or more or 800 (g / 1 mol) or less, and even more preferably 235 (g / 1 mol) or more or 650 (g / 1 mol) or less.

[0099] Examples of the aliphatic carbodiimide compound include diisopropylcarbodiimide and dioctyldecylcarbodiimide. Examples of the alicyclic carbodiimide compound include dicyclohexylcarbodiimide, poly(4,4'-dicyclohexylmethanecarbodiimide), and the like, with poly(4,4'-dicyclohexylmethanecarbodiimide) being particularly preferred. An example of a commercially available product is "Carbodilite" (product name; manufactured by Nisshinbo Chemical Co., Ltd.).

[0100] Examples of the aromatic carbodiimide compound include diphenylcarbodiimide, di-2,6-dimethylphenylcarbodiimide, N-triyl-N'-phenylcarbodiimide, di-p-nitrophenylcarbodiimide, di-p-aminophenylcarbodiimide, di-p-hydroxyphenylcarbodiimide, di-p-chlorophenylcarbodiimide, di-p-methoxyphenylcarbodiimide, di-3,4-dichlorophenylcarbodiimide, di-2,5-dichlorophenylcarbodiimide, di-o-chlorophenylcarbodiimide, p-phenylene-bis-di-o-triylcarbodiimide, p-phenylene-bis-dicyclohexylcarbodiimide, p-phenylene-bis-di-p-chlorophenylcarbodiimide, ethylene-bis-diphenyl Examples of the carbodiimide compounds include mono- or di-nylcarbodiimide compounds such as poly(4,4'-diphenylmethanecarbodiimide), poly(3,5'-dimethyl-4,4'-biphenylmethanecarbodiimide), poly(p-phenylenecarbodiimide), poly(m-phenylenecarbodiimide), poly(3,5'-dimethyl-4,4'-diphenylmethanecarbodiimide), poly(naphthylenecarbodiimide), poly(1,3-diisopropylphenylenecarbodiimide), poly(1-methyl-3,5-diisopropylphenylenecarbodiimide), poly(1,3,5-triethylphenylenecarbodiimide) and poly(triisopropylphenylenecarbodiimide), and two or more of these may be used in combination. Among these, di-2,6-dimethylphenylcarbodiimide, poly(4,4'-diphenylmethanecarbodiimide), poly(phenylenecarbodiimide) and poly(triisopropylphenylenecarbodiimide) are particularly preferably used. An example of a commercially available product is "Stavaxol P" (product name; manufactured by BASF).

[0101] (Compounds having an oxazoline group (ring)) Examples of the compound having an oxazoline group (ring) include oxazoline, alkyloxazoline (C1-4 alkyloxazoline such as 2-methyloxazoline and 2-ethyloxazoline), and bisoxazoline compounds.

[0102] Examples of the bisoxazoline compound include 2,2'-bis(2-oxazoline), 2,2'-bis(alkyl-2-oxazoline) [2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline) and other 2,2'-bis(C1-6 alkyl-2-oxazoline)], 2,2'-bis(aryl-2-oxazoline) [2,2'-bis(4-phenyl-2-oxazoline)], 2,2'-bis(cycloalkyl-2-oxazoline) [2, 2'-Bis(4-cyclohexyl-2-oxazoline), etc.], 2,2'-bis(aralkyl-2-oxazoline) [2,2'-bis(4-benzyl-2-oxazoline), etc.], 2,2'-alkylenebis(2-oxazoline) [2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), etc. 2,2'-C1-10 alkylenebis(2-oxazoline), etc.], 2,2'-alkylenebis(alkyl-2-oxazoline) [2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), etc. 2,2'-C1-10 alkylene bis(C1-6 alkyl-2-oxazoline) such as ethylene bis(4,4-dimethyl-2-oxazoline), etc.], 2,2'-arylene bis(2-oxazoline) [2,2'-(1,3-phenylene)-bis(2-oxazoline), 2,2'-(1,4-phenylene)-bis(2-oxazoline), 2,2'-(1,2-phenylene)-bis(2-oxazoline), 2,2'-diphenylene bis(2-oxazoline), etc.], 2,2'-arylene bis(alkyl-2-oxazoline) [2,2'-(1,3-phenylene)-bis(2-oxazoline), )-bis(4-methyl-2-oxazoline), 2,2'-(1,4-phenylene)-bis(4,4-dimethyl-2-oxazoline) and other 2,2'-phenylene-bis(C1-6 alkyl-2-oxazoline), etc.], 2,2'-aryloxyalkanebis(2-oxazoline) [2,2'-9,9'-diphenoxyethanebis(2-oxazoline), etc.], 2,2'-cycloalkylenebis(2-oxazoline) [2,2'-cyclohexylenebis(2-oxazoline), etc.], N,N'-alkylenebis(2-carbamoyl-2-oxazoline) [N,N,N'-C1-10 alkylene bis(2-carbamoyl-2-oxazoline) such as N'-ethylene bis(2-carbamoyl-2-oxazoline), N,N'-tetramethylene bis(2-carbamoyl-2-oxazoline), etc.], N,N'-alkylene bis(2-carbamoyl-alkyl-2-oxazoline) [N,N'-ethylene bis(2-carbamoyl-4-methyl-2-oxazoline)] Examples of the N,N'-C1-10 alkylene bis(2-carbamoyl-C1-6 alkyl-2-oxazoline) such as N,N'-tetramethylene bis(2-carbamoyl-4,4-dimethyl-2-oxazoline), N,N'-arylene bis(2-carbamoyl-2-oxazoline) [N,N'-phenylene bis(2-carbamoyl-oxazoline), etc.] can be given.

[0103] Compounds having an oxazoline group also include vinyl polymers containing an oxazoline group [such as Epocross RPS series, RAS series and RMS series, manufactured by Nippon Shokubai Co., Ltd.]. Among these oxazoline compounds, bisoxazoline compounds are preferred.

[0104] (Compounds having an oxazine group (ring)) As the compound having the oxazine group (ring), an oxazine or bisoxazine compound can be used.

[0105] Examples of the bisoxazine compound include 2,2'-bis(5,6-dihydro-4H-1,3-oxazine), 2,2'-bis(alkyl-5,6-dihydro-4H-1,3-oxazine) [2,2'-bis(C1-6 alkyl-5,6-dihydro-4H-1,3-oxazine) such as 2,2'-bis(4-methyl-5,6-dihydro-4H-1,3-oxazine), 2,2'-bis(4,4-dimethyl-5,6-dihydro-4H-1,3-oxazine), and 2,2'-bis(4,5-dimethyl-5,6-dihydro-4H-1,3-oxazine)], 2'-Alkylenebis(5,6-dihydro-4H-1,3-oxazine) [2,2'-methylenebis(5,6-dihydro-4H-1,3-oxazine), 2,2'-ethylenebis(5,6-dihydro-4H-1,3-oxazine), 2,2'-hexanemethylenebis(5,6-dihydro-4H-1,3-oxazine) and other 2,2'-C1-10 alkylenebis(5,6-dihydro-4H-1,3-oxazines)], 2,2'-arylenebis(5,6-dihydro-4H-1,3-oxazine) [2,2'-(1,3-phenylene)-bis(5,6-dihydro 2,2'-(1,4-phenylene)-bis(5,6-dihydro-4H-1,3-oxazine), 2,2'-(1,2-phenylene)-bis(5,6-dihydro-4H-1,3-oxazine), 2,2'-naphthylenebis(5,6-dihydro-4H-1,3-oxazine), 2,2'-diphenylenebis(5,6-dihydro-4H-1,3-oxazine), etc.], N,N'-alkylenebis(2-carbamoyl-5,6-dihydro-4H-1,3-oxazine) [N,N'-ethylenebis(2-carbamoyl-5,6-dihydro N,N'-C1-10 alkylene bis(2-carbamoyl-5,6-dihydro-4H-1,3-oxazine) [N,N'-ethylene bis(2-carbamoyl-4-methyl-5,6-dihydro-4H-1,3-oxazine), N,N'-hexamethylene bis(2-carbamoyl-4,4-dimethyl-5,Examples of the oxazine compounds include N,N'-C1-10 alkylene bis(2-carbamoyl-C1-6 alkyl-5,6-dihydro-4H-1,3-oxazine) and N,N'-arylene bis(2-carbamoyl-5,6-dihydro-4H-1,3-oxazine) [N,N'-phenylene bis(2-carbamoyl-oxazine)]. Among these oxazine compounds, bisoxazine compounds are preferred.

[0106] (Compounds containing carboxylic acids) Examples of the compound having a carboxylic acid include formic acid, acetic acid, propionic acid, acrylic acid, methacrylic acid, oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, adipic acid, benzoic acid, phthalic acid, terephthalic acid, lactic acid, malic acid, tartaric acid, diphenolic acid, benzenesulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, nonylbenzenesulfonic acid, nitrobenzenesulfonic acid, cyanobenzenesulfonic acid, hydroxybenzenesulfonic acid, methylsulfonic acid, trifluoromethanesulfonic acid, trifluoroacetic acid, nitrobenzenecarboxylic acid, cyanobenzenecarboxylic acid, hydroxybenzenecarboxylic acid, hydroxyacetic acid, and salts thereof.

[0107] (Compounds having an amide group) Examples of the compound having an amide group include (meth)acrylamide, N-methylmethacrylamide, methylolated acrylamide, methylolated methacrylamide, ureidovinyl ether, β-ureidoisobutylvinyl ether, and ureidoethyl acrylate.

[0108] <Reinforced filler (d)> The polyester resin composition (A) preferably contains a reinforcing filler (d) such as glass fiber. By containing the reinforcing filler (d), the strength, rigidity, and dimensional stability of the polyester resin composition (A) or the resin-metal composite can be improved.

[0109] The following description will focus on the case of glass fiber, which is particularly preferred as the reinforcing filler (d). The polyester resin composition (A) preferably contains 10 to 100 parts by mass of glass fiber per 100 parts by mass of the polyester resin composition (A). If the content is too small, the reinforcing effect may be insufficient, and if the content is too large, the appearance and impact resistance may be poor, and the flowability may be insufficient. From this viewpoint, a particularly preferred content of the glass fiber is, relative to 100 parts by mass of the polyester resin composition (A), 15 parts by mass or more, more preferably 20 parts by mass or more, and particularly preferably 25 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 50 parts by mass or less.

[0110] The type of glass fiber is not particularly limited, and examples thereof include glass fibers such as E glass, C glass, A glass, S glass, etc. Among these, alkali-free glass (E glass) fibers are preferred because they do not adversely affect the thermal stability of the polyester resin composition (A).

[0111] Two or more types of glass fibers may be used in combination depending on the required characteristics.

[0112] The average fiber diameter of the glass fibers is not particularly limited. It is preferable to select it within the range of 1 to 100 μm. If the average fiber diameter of the glass fibers is 1 μm or more, production is easy and the cost can be suppressed. On the other hand, if it is 100 μm or less, the tensile strength of the glass fibers can be maintained. In particular, from the viewpoint of increasing the bonding strength, the average fiber diameter of the glass fibers is more preferably 4 μm or more and 9 μm or less, of which 5 μm or more and 8 μm or less, and even more preferably 6 μm or more and 7 μm or less. The cross section of the fiber may be circular or flat.

[0113] The average fiber length of the glass fibers after molding the resin-metal composite is not particularly limited. However, if the average fiber length of the glass fibers is too short, the reinforcing effect may not be fully exhibited, and if it is too long, the bonding strength between the metal member (X) and the resin member (Y) of the resin-metal composite may decrease. From this viewpoint, the average fiber length is preferably 50 μm to 800 μm, more preferably 100 μm or more or 750 μm or less, even more preferably 150 μm or more or 700 μm or less, and even more preferably 200 μm or more or 650 μm or less. The average fiber length is the average value calculated by an image analyzer (WinROOF2015, manufactured by Mitani Shoji Co., Ltd.) from images of 2,000 glass fibers from the filler residue collected by processing such as high-temperature incineration of molded products, dissolution with a solvent, and decomposition with chemicals, observed with an optical microscope (B201, manufactured by OLYMPUS Corporation). In addition, the method of impregnating the periphery of a glass fiber roving with the polyester resin composition (A) to form long fiber pellets by a wire coating method is not preferred because it may reduce the bonding strength of the resin-metal composite.

[0114] The glass fibers used in the present invention may be surface-treated with a coupling agent such as aminosilane or epoxysilane in order to improve adhesion to the polyester resin composition (A). Examples of coupling agents include chlorosilane compounds such as vinyltrichlorosilane and methylvinyldichlorosilane; alkoxysilane compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane and γ-methacryloxypropyltrimethoxysilane; epoxysilane compounds such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane; acrylic compounds, isocyanate compounds, titanate compounds, and epoxy compounds.

[0115] The glass fibers used in the present invention are preferably used as chopped strands (chopped glass fibers) obtained by bundling a large number of these fibers and cutting them to a predetermined length, and in this case, it is preferable to blend a sizing agent into the glass fibers. By blending the sizing agent, the production stability of the polyester resin composition (A) is improved, and good mechanical properties can be obtained. The glass fiber sizing agent is not particularly limited, and examples thereof include resin emulsions of vinyl acetate resin, ethylene-vinyl acetate copolymer, acrylic resin, epoxy resin, polyurethane resin, polyester resin, etc., and preferably acrylic resin, epoxy resin, or polyurethane resin.

[0116] The polyester resin composition (A) preferably contains, in addition to the above-mentioned glass fibers, other inorganic fillers in the form of plates, particles or amorphous forms. The plate-like inorganic filler exhibits the function of reducing anisotropy and warpage, and examples thereof include talc, glass flakes, mica, kaolin, metal foil, etc. Among the plate-like inorganic fillers, glass flakes are preferred. Other particulate or amorphous inorganic fillers include, for example, ceramic beads, clay, zeolite, barium sulfate, titanium oxide, silicon oxide, aluminum oxide, magnesium hydroxide, zinc sulfide, and the like. As the other inorganic filler, talc, titanium oxide, and zinc sulfide are particularly preferred.

[0117] The polyester resin composition (A) preferably contains 10 to 100 parts by mass of an inorganic filler relative to 100 parts by mass of the polyester resin composition (A). If the content is too small, the reinforcing effect may be insufficient, while if the content is too large, the appearance and impact resistance may be poor, and the flowability may be insufficient. From this viewpoint, a particularly preferred content of the inorganic filler is, relative to 100 parts by mass of the polyester resin composition (A), 15 parts by mass or more, more preferably 20 parts by mass or more, and particularly preferably 25 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, even more preferably 60 parts by mass or less, and particularly preferably 50 parts by mass or less.

[0118] <Other ingredients> The polyester resin composition (A) may contain other components in addition to the above. Examples of the additives include stabilizers, release agents, colorants, elastomers, flame retardants, flame retardant assistants, anti-dripping agents, ultraviolet absorbers, antistatic agents, anti-fogging agents, lubricants, anti-blocking agents, plasticizers, dispersants, and antibacterial agents. As the elastomer, those described in paragraphs 0050 to 0076 of Japanese Patent No. 6604977 can be used. As the flame retardant, those described in paragraphs 0071 to 0076 of Japanese Patent No. 6518479 can be used.

[0119] <<Manufacturing method of this resin-metal composite>> Next, a method for producing the resin-metal composite will be described. The method for producing the resin-metal composite is not particularly limited, and can be, for example, insert molding.

[0120] <Insert molding> In the case of insert molding as described above, the metal member (X) having an uneven surface is placed in advance in a molding die, and the molten polyester resin composition (A) is then filled into the die and cooled. By insert molding in this manner, the uneven surface side of the metal member (X) can be joined to the resin member (Y) at the same time as molding the resin member (Y), making it possible to firmly and stably join the metal member (X) and the resin member (Y), which was previously difficult to achieve by strong joining or welding.

[0121] The polyester resin composition (A) may be prepared by a conventional method. Usually, the components and various additives added as required are mixed together and then melt-kneaded in a single-screw or twin-screw extruder. The resin composition of the present invention may also be prepared without premixing the components or by premixing only a portion of the components and feeding them to an extruder using a feeder for melt-kneading. When a fibrous reinforcing filler such as glass fiber is used, it is also preferable to feed it from a side feeder midway through the cylinder of the extruder.

[0122] The melting temperature of the polyester resin composition (A), in other words, the heating temperature during melt kneading, is preferably selected appropriately usually from the range of 220 to 300° C. If this temperature is too high, decomposition gas is likely to be generated, and therefore it is desirable to select a screw configuration taking into consideration shear heat generation, etc.

[0123] Examples of the molding method for filling the polyester resin composition (A) into a mold include injection molding, extrusion molding, compression molding, etc. Among these, injection molding is the most common.

[0124] On the other hand, the size and shape of the metal member (X) to be mounted in the mold may be appropriately determined depending on the size, structure, etc. of the resin-metal composite.

[0125] The size, shape, thickness, etc. of the resin-metal composite are not particularly limited, and may be any of a plate shape (disk, polygon, etc.), a column shape, a box shape, a bowl shape, a tray shape, etc. These shapes may be attached after shaping by casting, press molding, etc., before the metal member (X) is placed in the molding die, or may be shaped after compounding. Alternatively, the shape may be shaped in the die simultaneously with or immediately before injection molding using a composite molding machine equipped with a press function. In the case of a large or complicated composite, it is not necessary for the thickness of all parts of the composite to be uniform, and the composite may be provided with reinforcing ribs. The metal member (X) does not need to cover the entire resin-metal composite, but may be only a part of it.

[0126] When insert molding, optimizing the combination of the temperature of the molten polyester resin composition (A) and the temperature of the metal member (X) is useful in improving the bonding strength. As a method for this, there can be mentioned a method in which the metal member (X) to be placed in the mold is preheated, or a method in which the mold is heated.

[0127] Examples of methods for preheating the metal member (X) to be placed in the mold include induction heating the metal member (X) before insert molding, heating with an IH heater, hot plate, heating furnace, etc., inserting the metal member (X) into the mold and then externally heating the vicinity of the bonding area with the polyester resin composition with a halogen lamp, dryer, etc., inserting the metal member (X) into the mold and then heating inside the mold with a cartridge heater, etc. Among these, it is most useful to locally heat only the bonding area with the polyester resin composition (A). The term "locally heated" includes the case where the area including the joining area is heated depending on the heating means, but the area of ​​the metal member (X) far from the joining area is not heated.

[0128] When the mold is heated, if the temperature of the mold is too low, the inserted metal member (X) is not heated sufficiently, and there is a possibility that sufficient bonding strength is not obtained. In particular, in the case of the present resin-metal composite, since the resin needs to solidify after sufficiently penetrating the unevenness of the surface of the metal member (X), it is preferable to heat it locally as necessary to a higher temperature than usual. On the other hand, if the temperature is too high, there is a possibility that a good composite will not be obtained due to the effect on the resin itself. From this viewpoint, in the present method for producing a resin-metal composite, the surface temperature of the mold with which the metal member (X) attached to the mold comes into contact is preferably set to a temperature 60 to 100°C higher than the glass transition temperature of the polyester (a), and more preferably set to a temperature 65 to 95°C higher, even more preferably set to a temperature 68 to 95°C higher, and even more preferably set to a temperature 70 to 93°C higher.

[0129] <<Form of this resin-metal composite>> The resin-metal composite can be formed into any desired shape. As an example of the configuration of this resin-metal composite, as shown in Figures 1 and 2, a resin member (Y) shaped as an in-vehicle part can be provided with a peripheral wall portion Y1 that surrounds the peripheral edge portion of a plate-shaped metal member (X).

[0130] The metal member (X) is formed by subjecting the joining area of ​​a plate-shaped metal base to an uneven surface by an uneven treatment, and as shown in Figure 2, at the peripheral edge of the metal member (X), the resin member (Y) covers the edge portion on the front side of the metal member (X) via the end face to the edge portion on the back side, and the edge portion on the front side and the edge portion on the back side of the metal member (X) are joined to the polyester resin composition (A) of the resin member (Y) at the edge portion on the front side and the edge portion on the back side of the metal member (X) (joint (J)).

[0131] 1 and 2 are merely examples. The shapes of the metal member (X) and the resin member (Y) can be changed as desired. Furthermore, the resin-metal composite can be formed by combining various shapes of metal members (X) and various shapes of resin members (Y).

[0132] As shown in Figs. 3(a) to (e), the state of bonding between the metal member (X) and the resin member (Y) can also be changed as desired. For example, as shown in FIG. 3(a), a metal member (X) may be used in which one side of a metal base is roughened to form an uneven surface on the metal surface, and at the peripheral edge of the metal member (X), a resin member (Y) covers the edge of the metal member (X) from the edge on the front side to the edge on the back side via the edge face, and the uneven surface of the metal member (X) and the resin member (Y) may be joined only on one side of the edge of the metal member (X) (joint (J)). As shown in Figure 3(b), the metal member (X) may be one obtained by performing an unevenness treatment on one side of a metal base to form unevenness on the metal surface, and at the peripheral end of the metal member (X), the resin member (Y) may cover the edge portion to the end face of the front side of the metal member (X), and the uneven surface of the metal member (X) and the resin member (Y) may be joined only on one side of the edge portion of the metal member (X) (joint (J)).

[0133] As shown in Figure 3 (c), the metal member (X) may be one in which one side of a metal base is subjected to an unevenness treatment to form unevenness on the metal surface, and an edge portion of one surface of the metal member (X) and an edge portion of one surface of the resin member (Y) may overlap with each other with an appropriate width, and the uneven surface of the metal member (X) and the resin member (Y) may be joined at this portion (joint (J)). As shown in Figure 3 (d), the metal member (X) may be one in which both sides of a metal base are subjected to an unevenness treatment to form unevenness on the metal surface, and at the peripheral edge of the metal member (X), a resin member (Y) covers the edge to the end face on the front side of the metal member (X), and the uneven surface of the metal member (X) and the resin member (Y) are joined only on one side of the edge of the metal member (X) (joint (J)). As shown in Figure 3 (e), the metal member (X) may be one in which both sides of a metal base are subjected to an unevenness treatment to form unevenness on the metal surface, and an edge portion of one surface of the metal member (X) and an edge portion of one surface of the resin member (Y) may overlap with each other with an appropriate width, and the uneven surface of the metal member (X) and the resin member (Y) may be joined at this portion (joint (J)).

[0134] The ratio (S1 / S2) of the bonding area (S1) between the metal member (X) and the resin member (Y) to the area (S2) of the metal member (X) that is exposed and not covered by the resin member (Y) is preferably larger, since this leads to more stable adhesion and improved airtightness. Specifically, the ratio (S1 / S2) is preferably 0.01 or more, more preferably 0.1 or more, and particularly preferably 0.5 or more, since sufficient airtightness can be obtained. In order to ensure heat dissipation from the exposed metal parts, it is preferable that the ratio (S1 / S2) is relatively small. Specifically, the ratio (S1 / S2) is preferably 8 or less, more preferably 4 or less, even more preferably 2 or less, and is particularly preferably 1 or less, since sufficient heat dissipation can be ensured.

[0135] By bonding with the S1 / S2 ratio in this way, the bonding strength and airtightness can be increased, and when used as a component of a housing, the heat trapped inside the housing can be sufficiently released, ensuring heat dissipation. When the metal surface is provided with projections and recesses on both sides, the joint area between the projections and recesses on the metal member (X) and the resin member (Y), i.e., the area of ​​the joints (J) (J), does not need to be the same on both sides.

[0136] <<Bonding strength of this resin-metal composite>> This resin-metal composite has a structure in which the uneven surface of the metal member (X) is bonded to the resin member (Y), thereby enabling it to have excellent bond strength. Specifically, it is possible to realize an initial bond strength of 20 MPa or more.

[0137] In the present invention, the term "bonding strength" refers to a value obtained by preparing a test piece for a bond strength test having a shape described in the Examples, bonding a metal member (X) and a resin member (Y) using the bonding conditions for producing a resin-metal composite, and performing a tensile test described in the Examples on the obtained composite.

[0138] (airtightness) This resin-metal composite undergoes a heat shock test in which one cycle is a treatment process of -40°C for one hour followed by a treatment process of 150°C for one hour, and after performing this treatment process 100 cycles, the airtightness of the composite can be 0.5 MPa or more, preferably 0.6 MPa or more, more preferably 0.8 MPa or more, and even more preferably 1.0 MPa or more.

[0139] <<Applications of this resin-metal composite>> The resin-metal composite can firmly and stably bond a metal member and a resin member, can obtain excellent bonding strength, and can combine the properties of both, such as heat dissipation, heat resistance, insulation, and antistatic properties, and can be suitably used for various applications, particularly for automotive applications where bonding strength and heat dissipation are particularly required.

[0140] Specifically, when a container is formed using this resin-metal composite, the container can have excellent airtightness, heat dissipation, heat resistance, insulation, antistatic properties, etc., and can therefore be suitably used in applications that require bonding strength as a function, such as components that constitute all or part of the casing of general home appliances and electric / electronic components (housings, cases, covers, etc.) incorporated into office equipment, machine mechanism components, and vehicle electrical components (various control units, ignition coil components, sensor components, motor components, power modules, step-up DC / DC converters, step-down DC / DC converters, capacitors, insulators, motor terminal blocks, batteries, electric compressors, battery current sensors, junction blocks, etc.).

[0141] FIG. 4 shows an example in which this resin-metal composite is used as part of the housing for an electrical component in a vehicle. When the resin-metal composite is used as a part of a product, that is, when it is used in combination with another member (Z) (such as a resin molded body, an aluminum die-cast, or a metal), any method can be used to join the resin-metal composite to the other member (Z), for example, to join the resin member (Y) to the other member (Z). Examples of the method include laser welding, ultrasonic welding, vibration welding, heat welding, mechanical joining using bolts or tapping screws, and adhesives.

[0142] <<Explanation of terms>> In the present invention, when it is described as "X to Y" (X and Y are any numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as the meaning of "preferably larger than X" or "preferably smaller than Y". In addition, when it is stated that the amount is "X or more" (X is any number), it also means that the amount is "preferably greater than X" unless otherwise specified, and when it is stated that the amount is "Y or less" (Y is any number), it also means that the amount is "preferably smaller than Y" unless otherwise specified. EXAMPLES

[0143] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples without departing from the gist of the present invention.

[0144] <Surface treatment of metal components> A metal plate made of an aluminum alloy (JIS H4000 "A5052") in the shape of a strip measuring 45 mm in length, 12 mm in width, and 1.5 mm in thickness was immersed in the following zincate solution (40.0°C) for 60 seconds. Next, the metal plate was immersed in the following etching agent (50°C) for 480 seconds to roughen the surface of the metal plate to form an uneven surface. Next, the metal plate was immersed in a commercially available zirconium conversion treatment agent (Palseed (registered trademark) manufactured by Nippon Parkerizing Co., Ltd., concentration 50 g / L, temperature 45°C, pH 4.0) for 120 seconds to obtain a metal member (X).

[0145] <Zincate liquid components> ·water Zinc oxide: 0.25 mol / L Sodium hydroxide: 3.80 mol / L ·Tartaric acid: 0.07mol / L pH: 12.5

[0146] <Etching agent components> ·water Sodium peroxodisulfate: 0.35 mol / L Sodium chloride: 1.70 mol / L pH: 3.0

[0147] The uneven surface of the metal member (X) treated as described above was observed with a 20x objective lens of a hybrid laser microscope (OPTELICS HYBRID manufactured by LASERTEC), and the surface roughness was measured in accordance with JIS B 0601:2001 using the attached analysis software (Lasertec Microscope Solution Software LMeye7) at a 20x objective lens. The measurement was performed using the Fine Peak measurement algorithm to obtain an FZ image of the average uneven surface at the center of a rectangular metal plate made of aluminum alloy (JIS H4000 "A5052") 45 mm long, 12 mm wide, and 1.5 mm thick. The measurement range was 4.2 mm long in the 45 mm vertical direction. The cutoff value λc was 0.8000 mm. The same operation was repeated 30 times at random different locations, and the average values ​​were calculated, resulting in an arithmetic mean roughness (Ra) of 5.2 μm and a maximum height (Rz) of 34.7 μm. The size distribution was a combination of large recesses with an opening diameter and / or depth of 80 to 150 μm and small recesses with an opening diameter and / or depth of 1 to 5 μm. The small recesses were distributed within and around the large recesses.

[0148] [Table 1]

[0149] [Table 2]

[0150] (Preparation of polyester resin compositions α1 to α7) The components shown in Table 1, except for the reinforcing filler (D), were mixed uniformly in a tumbler mixer in the proportions shown in Table 2 (all parts by weight). Then, a co-rotating twin screw extruder (Japan Steel Works, Ltd., "TEX-30α", screw diameter 32 mm, L / D = 52) was used, and the reinforcing filler (D) was fed from a side feeder at 40 kg / hr. The extruder barrel temperature C1 to C15 was set at 260 ° C, the die at 250 ° C, and the screw rotation speed was 200 rpm. The extruder was melt-kneaded under the conditions of 4 nozzles (circular (φ4 mm), length 1.5 cm), shear rate (γ) 211 sec -1 The strand was extruded under the conditions of 270°C immediately after extrusion. The extruded strand was rapidly cooled in a water bath adjusted to a temperature range of 30-50°C. The strand surface temperature (T) was cooled to 65°C as measured by an infrared thermometer (γ T = 1.4 × 10 4 ), and was inserted into a pelletizer and cut to obtain pellets of polybutylene terephthalate resin compositions α1 to 7. The resulting pellets of polyester resin compositions α1 to α7 were dried at 120° C. for 5 hours and then used for insert molding.

[0151] <Examples 1 to 5, Comparative Examples 1 to 2> The metal member (X) prepared as above was placed in a mold cavity, and the pellets of the polyester resin compositions α1 to α13 obtained above were injection molded under the conditions shown below to obtain a resin-metal composite (evaluation sample) in which the metal member (X) and the resin member (Y) made of the polyester resin composition (A) were bonded together, as shown in Figure 5. At this time, the bonding area between the metal member (X) and the resin member (Y) was 5 mm x 10 mm. Injection molding conditions: The injection molding machine used was a "J85AD" manufactured by Japan Steel Works, Ltd. The conditions were as follows: cylinder temperature 270°C, mold temperature 140°C, injection speed 60 mm / sec, filling time 0.2 sec, holding pressure 110 MPa, holding time 10 sec, cooling time 30 sec. The above mold temperature indicates the temperature of the mold surface with which the metal member (X) comes into contact.

[0152] <Evaluation and measurement methods> The resin-metal composites (evaluation samples) obtained in the examples and comparative examples were measured and evaluated by the following methods.

[0153] (Initial bond strength) Using the resin-metal composites (evaluation samples) obtained in the Examples, Comparative Examples, and Reference Examples, the initial bonding strength was measured in accordance with ISO19095 as follows. Using a tensile tester (Instron Model 5544), a tensile test (tensile speed 5 mm / min) was performed in the vertical direction to the joint surface of the end of the obtained resin-metal composite (evaluation sample) to measure the maximum tensile stress of the joint surface, i.e., the joint strength. The obtained strength is shown in the "Initial joint strength" column in Table 3.

[0154] (Breaking stress test) The resin composition pellets obtained above were dried at 120°C for 5 hours, and then injection molded into ISO dumbbell pieces (4 mm thick) using an injection molding machine (NEX80 manufactured by Nissei Plastics Co., Ltd.) under conditions of a cylinder temperature of 260°C and a mold temperature of 80°C. The ISO dumbbell specimens obtained above were measured for breaking stress (unit: MPa) in accordance with ISO standards 527-1 and ISO 527-2.

[0155] (Bending strength test) The pellets of polyester resin compositions α1 to α7 obtained by the above method were dried at 70°C for 3 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (manufactured by Toshiba Machine Co., Ltd., "EC75SX") under conditions of a cylinder temperature of 300°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. In accordance with ISO178, the flexural strength (unit: MPa) was measured at a temperature of 23°C using the above ISO tensile test pieces (4 mm thick).

[0156] (Gas generation test) Using the pellets of the polyester resin compositions α1, α3 and α6 obtained by the above method, a gas generation amount test was carried out by the following mold deposit evaluation.

[0157] [Mold deposit evaluation] The molding machines and conditions used for the evaluation are as follows: Injection molding machine: SE18 manufactured by Sumitomo Heavy Industries, Ltd. Injection pressure: 50MPa Injection speed: 80mm / sec Cylinder temperature 270℃ Injection time 3sec Cooling 8sec Mold temperature 35℃ Suckback 3mm Molded product: Length 35mm, width 14mm, thickness 2mm Mold Pin gate mold

[0158] Injection molding was performed continuously under the above conditions. After 300 shots, the state of the mold deposit adhering to the mold (mold contamination) was observed with the naked eye and rated on a scale of 10 points, with the best mold deposit state being given a score of 10. The above evaluation results are shown in Table 3. In the table, "-" indicates that the measurement was not performed.

[0159] (Evaluation of releasability during continuous molding) In the mold deposit evaluation test, 300 shots of continuous molding were carried out, and the mold releasability during continuous molding was evaluated according to the following criteria. ○ (good): There was little sticking to the mold when releasing, making automatic continuous molding possible. × (poor): The part frequently stuck to the mold when released, making automatic continuous molding difficult.

[0160] [Table 3]

[0161] (Consideration) As is clear from the above results, it was found that the resin composition of the present invention has a small amount of gas. In particular, since the amount of gas was reduced in Example 1, it was found that the amount of gas can be reduced by using oxidized polyethylene wax. Furthermore, it was found that Examples 1 to 5 have higher releasability during continuous molding than Comparative Example 2, and that the releasability is improved by the low molecular weight compound. Furthermore, Example 1, which used glass fibers with an average fiber diameter of 6.5 μm, had improved fracture stress and bending strength compared to Example 2, which used glass fibers with an average fiber diameter of 13 μm, and it was found that the physical properties of the resin are improved when small-diameter glass is used. From this, it is preferable that the average fiber diameter of the glass fibers is at least less than 13 μm, and it is expected that the physical properties of the resin will be improved if the average fiber diameter is within the range of ±2.5 μm of 6.5 μm.

[0162] (Preparation of polyester resin compositions α8 to α13) Similarly to the polyester resin compositions α1 to 7, polyester resin compositions α8 to 13 were prepared using the components and proportions shown in Table 4 (all parts by mass).

[0163] [Table 4]

[0164] <Examples 6 to 9 and Comparative Examples 3 to 4> Resin-metal composites (evaluation samples) were produced in the same manner as in Example 1, except that the polyester resin compositions α8 to α13 were used instead of the polyester resin compositions α1 to 7, and evaluated in the same manner as in Example 1 and the like.

[0165] [Table 5]

[0166] (Consideration) Even when the amount of glass was reduced, Examples 6 and 8, which used glass fibers with an average fiber diameter of 6.5 μm, had improved breaking stress and bending strength compared to Example 7, which used glass fibers with an average fiber diameter of 13 μm. Therefore, it is preferable that the average fiber diameter of the glass fibers is at least less than 13 μm, and it is expected that the breaking stress and bending strength will be improved especially if the average fiber diameter is within the range of ±2.5 μm of 6.5 μm.

[0167] <<Reference Example>> Hereinafter, specific examples (referred to as "Reference Examples") used as references in the present invention will be described.

[0168] <Surface treatment of metal components> A metal plate made of an aluminum alloy (JIS H4000 "A5052") in the shape of a strip measuring 45 mm in length, 12 mm in width, and 1.5 mm in thickness was immersed in the following zincate solution (40.0°C) for 60 seconds. Next, the metal plate was immersed in the following etching agent (50°C) for 480 seconds to roughen the surface of the metal plate to form an uneven surface. Next, the metal plate was immersed in a commercially available zirconium conversion treatment agent (Palseed (registered trademark) manufactured by Nippon Parkerizing Co., Ltd., concentration 50 g / L, temperature 45°C, pH 4.0) for 120 seconds to obtain a metal member (X).

[0169] <Zincate liquid components> ·water Zinc oxide: 0.25 mol / L Sodium hydroxide: 3.80 mol / L ·Tartaric acid: 0.07mol / L pH: 12.5

[0170] <Etching agent components> ·water Sodium peroxodisulfate: 0.35 mol / L Sodium chloride: 1.70 mol / L pH: 3.0

[0171] The uneven surface of the metal member (X) treated as described above was observed with a 20x objective lens of a hybrid laser microscope (OPTELICS HYBRID manufactured by LASERTEC), and the surface roughness was measured in accordance with JIS B 0601:2001 using the attached analysis software (Lasertec Microscope Solution Software LMeye7) at a 20x objective lens. The measurement was performed using the Fine Peak measurement algorithm to obtain an FZ image of the average uneven surface at the center of a rectangular metal plate made of aluminum alloy (JIS H4000 "A5052") 45 mm long, 12 mm wide, and 1.5 mm thick. The measurement range was 4.2 mm long in the 45 mm vertical direction. The cutoff value λc was 0.8000 mm. The same operation was repeated 30 times at random different locations, and the average values ​​were calculated, resulting in an arithmetic mean roughness (Ra) of 5.2 μm and a maximum height (Rz) of 34.7 μm. The size distribution was a combination of large recesses with an opening diameter and / or depth of 80 to 150 μm and small recesses with an opening diameter and / or depth of 1 to 5 μm. The small recesses were distributed within and around the large recesses.

[0172] [Table 6]

[0173] [Table 7]

[0174] (Preparation of polyester resin compositions α101 to 113) Among the components shown in Table 6, each component except for the reinforcing filler (D) was uniformly mixed in the ratios shown in Table 7 (all parts by mass) in a tumbler mixer, and then a co-rotating twin screw extruder (Japan Steel Works, Ltd. "TEX-30α", screw diameter 32 mm, L / D = 52) was used, and the reinforcing filler (D) was fed from a side feeder at 40 kg / hr. The extruder barrel temperature C1 to C15 was set at 260 ° C, the die was set at 250 ° C, and the screw rotation speed was set at 200 rpm. The extruder was melt-kneaded under the conditions of 4 nozzles (circular (φ4 mm), length 1.5 cm), and shear rate (γ) 211 sec ―1 The strand was extruded under the conditions of 270°C immediately after extrusion. The extruded strand was rapidly cooled in a water bath adjusted to a temperature range of 30-50°C. The strand surface temperature (T) was cooled to 65°C as measured by an infrared thermometer (γ T = 1.4 × 10 4 ), and the mixture was inserted into a pelletizer and cut to obtain pellets of the polybutylene terephthalate resin compositions α101 to α113. The resulting pellets of the polyester resin compositions α101 to α113 were dried at 120° C. for 5 hours and then used for insert molding.

[0175] <Reference Examples 1 to 2, 4 to 10, Reference Comparative Examples 1 to 4, Reference Example 1> The metal member (X) prepared as above was placed in a mold cavity, and the pellets of the polyester resin compositions α101 to α113 obtained above were injection molded under the conditions shown below to obtain a resin-metal composite (evaluation sample) in which the metal member (X) and the resin member (Y) made of the polyester resin composition (A) were bonded together, as shown in Figure 5. At this time, the bonding area between the metal member (X) and the resin member (Y) was 5 mm × 10 mm. Injection molding conditions: The injection molding machine used was a "J85AD" manufactured by Japan Steel Works, Ltd. The conditions were as follows: cylinder temperature 270°C, mold temperature 140°C, injection speed 60 mm / sec, filling time 0.2 sec, holding pressure 110 MPa, holding time 10 sec, cooling time 30 sec. In the local heating in Reference Example 2, a cartridge heater disposed inside the mold was used to locally heat only the bonding area with the metal member (X) to 160°C. The above mold temperature indicates the temperature of the mold surface with which the metal member (X) comes into contact.

[0176] <Reference Example 3> A resin-metal composite (evaluation sample) was obtained in the same manner as in Reference Example 1, except that a plate material of cast aluminum (ADC12) was used as the metal member.

[0177] <Evaluation and measurement methods> The resin-metal composites (evaluation samples) obtained in the reference examples and reference comparative examples were measured and evaluated by the following methods.

[0178] (Bonding strength test) A bonding strength test was carried out in accordance with ISO19095 using the resin-metal composites (evaluation samples) obtained in the Reference Examples, Reference Comparative Examples, and Reference Examples. Using a tensile tester (Instron Model 5544), a tensile test (tensile speed 5 mm / min) was performed in the vertical direction on the bonded surface of the end of the obtained resin-metal composite (evaluation sample) to measure the maximum tensile stress of the bonded surface, i.e., the bond strength. The obtained strength is recorded in the "Bond strength" column for 0 hr in Table 8 as the bond strength before the durability evaluation was performed.

[0179] [Table 8]

[0180] In the evaluation of the bonding property, all of Reference Examples 1 to 10 showed higher bonding strength than Reference Comparative Example. This is considered to be because the addition of the epoxy group-containing compound, which is a polyester terminal reactive compound, to the polyester resin composition (A) caused the reactive compound on the metal surface to react with the polyester terminal reactive compound, resulting in a stronger anchor effect, thereby improving the bonding strength.

[0181] Furthermore, from these results and the results of tests conducted by the inventors up to now, it was found that in order to increase the bonding strength, it is optimal to select 2,2-bis(4-hydroxyphenyl)-propane (bisphenol A type epoxy compound) as the epoxy group-containing compound to be combined with homo-PBT or copolymer PBT.

[0182] (Preparation of polyester resin compositions α114 to 120) Similarly to the polyester resin compositions α101 to 113, polyester resin compositions α114 to 120 were prepared in the proportions shown in Table 9 (all parts by mass).

[0183] [Table 9]

[0184] <Reference Examples 11 to 15, Reference Comparative Examples 5 to 6> Resin-metal composites (evaluation samples) were produced in the same manner as in Reference Example 1, except that the polyester resin compositions α114-120 were used instead of the polyester resin compositions α101-113. The results of the bonding strength test are shown in Table 10.

[0185] [Table 10]

[0186] From this result and the results of tests conducted by the inventors up to now, it has been found that the bonding strength can be further increased by adding a low molecular weight compound having a melting point of 40 to 140°C and a number average molecular weight of less than 6000 to the polyester resin composition (A).

[0187] <Reference Examples 16 to 18, Reference Comparative Examples 6 and 7> As shown in FIG. 6, a metal plate made of an aluminum alloy (JIS H4000 "A5052") was cut into a disk shape with a diameter of 55 mm and a thickness of 2 mm and a hole with a diameter of 20 mm was drilled in the center. The surface of the metal plate was treated in the same manner as in <Surface treatment of a metal member> described above to produce a metal member (X). The metal member (X) prepared as described above was placed in a mold cavity, and the pellets of the polyester resin composition α1 or α13 obtained above were injection molded under the conditions shown below to obtain a disk-shaped member having a diameter of 24 mm and a thickness of 2 mm, as shown in FIG. 6, in which the polyester resin composition (A) was arranged so as to overlap the metal member (X) and cover the central hole of the metal member (X), thereby obtaining a resin-metal composite (evaluation sample) in which the metal member (X) and the resin member (Y) made of the polyester resin composition (A) were bonded. At this time, the bonding width between the metal member (X) and the resin member (Y) was 2 mm, and the bonding area was 0.00013816 m. 2 It was. Injection molding conditions: The injection molding machine used was a "J85AD" manufactured by Japan Steel Works, Ltd. The conditions were as follows: cylinder temperature 270°C, mold temperature 140°C, injection speed 60 mm / sec, filling time 0.2 sec, holding pressure 110 MPa, holding time 10 sec, cooling time 30 sec.

[0188] <Evaluation and measurement methods> The resin-metal composites (evaluation samples) obtained in the reference examples and reference comparative examples were measured and evaluated by the following methods.

[0189] (Airtightness test) An airtightness test was carried out using the resin-metal composites (evaluation samples) obtained in the reference examples and reference comparative examples. The test was carried out using the evaluation pressure vessel shown in FIG. The pressure device for evaluation was created in the following shape. A SUS304 metal with a diameter of 90 mm was used, and a hole with a diameter of 30 mm and a depth of 20 mm was drilled in the center and filled with water. A hole with a diameter of 56 mm and a depth of 0.5 mm was drilled in the periphery, and a disk-shaped resin-metal composite (evaluation sample) obtained in the reference example and reference comparative example was attached via a Viton O-ring, and the metal was fixed with bolts using a SUS304 pressing plate with a diameter of 90 mm and a thickness of 8 mm, and immersed in water at 25°C. Next, water was pumped into the weld at 16 mL / 5 seconds using a test pump (TP50N made by Asada Co., Ltd.), and the internal pressure of the weld was gradually increased, and the water pressure at the time when the pressure was released from the joint (when the pressure dropped) was measured using a pressure sensor (GP-M025 made by Keyence Co., Ltd.). The obtained pressure is recorded in the "0 hr" column of Table 11 as the airtightness before the durability evaluation was performed.

[0190] (Durability evaluation) For the disk-shaped resin-metal composites (evaluation samples) obtained in the reference examples and reference comparative examples, a heat shock resistance test was carried out for 60 and 100 cycles using a thermal shock tester (TSA-103ES-W manufactured by Espec Corporation), in which one cycle was a treatment at -40°C for 1 hour followed by a treatment at 150°C for 1 hour. The airtightness (maximum water pressure at the time when pressure was released from the joint) of the samples after each exposure was measured. The results are shown in Table 11.

[0191] [Table 11]

[0192] In the evaluation of airtightness, all of Reference Examples 16 to 18 showed higher airtightness than Comparative Examples. This is believed to be because the addition of the polyester end reactive compound to the polyester resin composition (A) caused the reactive compound on the metal surface to react with the polyester end reactive compound, resulting in a stronger anchor effect, improving airtightness. [Explanation of symbols]

[0193] (X)...Metal parts (Y) Plastic parts Y1...peripheral wall part (J)·Joint part (Z) Other materials

Claims

1. A resin-metal composite comprising a metal member (X) having a surface with surface irregularities, and a resin member (Y) made of a polyester resin composition (A) containing a polyester (a) as a main component resin, the resin member (Y) being bonded to the surface side of the metal member (X) having surface irregularities, The polyester resin composition (A) contains, as a polyester (a), polybutylene terephthalate (also referred to as "homo-PBT"), a copolymer of polybutylene terephthalate (also referred to as "copolymerized PBT"), or a mixed resin thereof, and further contains an epoxy group-containing compound (b), a low molecular weight compound (c), and a reinforcing filler (d); The low molecular weight compound (c) comprises an oxidized polyethylene wax; The resin-metal composite is characterized in that the reinforcing filler (d) is a glass fiber having an average fiber diameter of 4 μm to 9 μm.

2. The polyester resin composition (A) has a ratio of the homo-PBT and copolymer PBT to the polymer components (excluding elastomers and flame retardants) constituting the composition (A) of 80 to 100 mass%. The resin-metal composite according to claim 1.

3. The polyester (a) has an intrinsic viscosity of 0.30 to 2.00 dl / g measured at 30 ° C. in a mixed solvent of tetrachloroethane and phenol in a 1:1 (mass ratio) mixture. The resin-metal composite according to claim 1 or 2.

4. The resin-metal composite according to any one of claims 1 to 3, characterized in that it contains a low molecular weight compound (c) in a ratio of 0.001 to 1.5 parts by mass per 100 parts by mass of the polyester resin composition (A).

5. 5. The resin-metal composite according to claim 1, wherein the oxidized polyethylene wax is an oxidized polyethylene wax having a number average molecular weight of 1,500 to 5,000.

6. The resin-metal composite according to any one of claims 1 to 5, characterized in that the low molecular weight compound (c) has an acid value of 0.01 to 40 mg / KOH.

7. The resin-metal composite according to any one of claims 1 to 5, characterized in that the low molecular weight compound (c) has an acid value of 0.5 to 20 mg / KOH.

8. The resin-metal composite according to claim 1, wherein the epoxy group-containing compound (b) is a 2,2-bis(4-hydroxyphenyl)-propane type epoxy compound or a novolac type epoxy compound.

9. The uneven surface of the metal member (X) has an arithmetic mean roughness (Ra) measured in accordance with JIS B 0601:2001 of 0.05 μm or more and 200 μm or less, and a maximum height (Rz) of 0.01 μm or more and 200 μm or less. The resin-metal composite according to any one of claims 1 to 8, characterized in that

10. A resin-metal composite according to any of claims 1 to 8, wherein the uneven surface of the metal member (X) has an arithmetic mean roughness (Ra) of 1 μm to 10 μm, measured in accordance with JIS B 0601:2001, and a maximum height Rz of 10 μm to 50 μm, and is a surface on which recesses having an opening diameter and / or depth of 50 μm or more and 200 μm or less and recesses having an opening diameter and / or depth of 0.5 μm or more and 10 μm or less are distributed coexisting.

11. The surface of the metal member (X) is provided with an oxide film, a chemical conversion film, a plating layer, a silane coupling agent treatment layer, a primer layer, or another resin layer, or fine particles are fixed to the surface. The resin-metal composite according to any one of claims 1 to 10.

12. The resin member (Y) covers the edge portion on the back side of the metal member (X) from the edge portion on the front side via the end face, and the edge portion on the front side and the edge portion on the back side of the metal member (X) are bonded to the polyester resin composition (A) of the resin member (Y) at the edge portion on the front side and the edge portion on the back side of the metal member (X). The resin-metal composite according to any one of claims 1 to 11, comprising a configuration in which the surface side of the metal member (X) and the polyester resin composition (A) of the resin member (Y) are bonded to each other.

13. The method for producing a resin-metal composite according to any one of claims 1 to 12, A method for producing a resin-metal composite, comprising the steps of: mounting a metal member (X) in a molding die in advance; filling the die with a molten polyester resin composition (A) and cooling the composition to bond an uneven surface side of the metal member (X) to a resin member (Y); A method for producing a resin-metal composite, characterized in that the surface temperature of a mold with which the metal member (X) attached to the mold comes into contact is set to a temperature 60 to 100° C. higher than the glass transition temperature of the polyester (a).

14. A vehicle member comprising the resin-metal composite according to any one of claims 1 to 12.

15. An electrical component comprising the resin-metal composite according to any one of claims 1 to 12.

16. A housing member comprising the resin-metal composite according to any one of claims 1 to 12.

17. A housing member for an electrical component for a vehicle, comprising the resin-metal composite according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Casing for electronic apparatus

    JP1994029669A

  • Surface treatment of metal and metallic member having surface obtained by this surface treatment method

    JP1999293476A

  • Composite of metal and resin, and its manufacturing method

    JP2008173967A

  • Polyester resin composition and light reflector

    JP2008280498A

  • Metal / plastic composite and its manufacturing process

    JP2010064397A